Criminology: Some lines of flight - Berg, Julie (Journal of criminology, 2021)
The 40th Anniversary Edition of Taylor, Walton and Young?s New Criminology, published in 2013, opened with these words: ?The New Criminology was written at a particular time and place, it was a product of 1968 and its aftermath; a world turned upside down?. We are at a similar moment today. Several developments have been, and are turning, our 21st century world upside down. Among the most profound has been the emergence of a new earth, that the ?Anthropocene? references, and ?cyberspace?, a term first used in the 1960s, which James Lovelock has recently termed a ?Novacene?, a world that includes both human and artificial intelligences. We live today on an earth that is proving to be very different to the Holocene earth, our home for the past 12,000?years. To appreciate the Novacene one need only think of our ?smart? phones. This world constitutes a novel domain of existence that Castells has conceived of as a terrain of ?material arrangements that allow for simultaneity of social practices without territorial contiguity? ? a world of sprawling material infrastructures, that has enabled a ?space of flows?, through which massive amounts of information travel. Like the Anthropocene, the Novacene has brought with it novel ?harmscapes?, for example, attacks on energy systems. In this paper, we consider how criminology has responded to these harmscapes brought on by these new worlds. We identify ?lines of flight? that are emerging, as these challenges are being met by criminological thinkers who are developing the conceptual trajectories that are shaping 21st century criminologies.